The first report of porcine parvovirus 7 (PPV7) in Colombia demonstrates the presence of variants associated with modifications at the level of the VP2-capsid protein (2021)
There are a wide variety of porcine parvoviruses (PPVs) referred to as PPV1 to PPV7. The latter was discovered in 2016 and later reported in some countries in America, Asia, and Europe. PPV7 as a pathogenic agent or coinfection with other pathogens causing disease has not yet been determined. In the present study, we report the identification of PPV7 for the first time in Colombia, where it was found retrospectively since 2015 in 40% of the provinces that make up the country (13/32), and the virus was ratified for 2018 in 4/5 provinces evaluated. Additionally, partial sequencing (nucleotides 380 to 4000) was performed of four Colombian strains completely covering the VP2 and NS1 viral genes. A sequence identity greater than 99% was found when comparing them with reference strains from the USA and China. In three of the four Colombian strains, an insertion of 15 nucleotides (five amino acids) was found in the PPV7-VP2 capsid protein (540–5554 nt; 180–184 aa). Based on this insertion, the VP2 phylogenetic analysis exhibited two well-differentiated evolutionarily related groups. To evaluate the impact of this insertion on the structure of the PPV7-VP2 capsid protein, the secondary structure of two different Colombian strains was predicted, and it was determined that the insertion is located in the coil region and not involved in significant changes in the structure of the protein. The 3D structure of the PPV7-VP2 capsid protein was determined by threading and homology modeling, and it was shown that the insertion did not imply a change in the shape of the protein. Additionally, it was determined that the insertion is not involved in suppressing a potential B cell epitope, although the increase in length of the epitope could affect the interaction with molecules that allow a specific immune response.